Association of edaphic factors with herbal plants abundance and density in a recreational forest, Terengganu, Peninsular Malaysia - Khairil, M.; Siti Meriam, A.; Nur Fatihah, H.N.; Nashriyah, M.; Razali, M.S.; Noor-Amalina, R. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Terengganu is one of the states in East Coast Peninsula Malaysia that provides the natural habitat for the herbal plants and non-tree plants. The question of the relationship between herbal and non-tree plants, their abundance and relationship with edaphic factor is still unsolved. This study was conducted at Chemerong Recreational Forest, Dungun, Terengganu to determine the abundance and diversity of herbal and non-tree plants species, and its relationship with the physico-chemical soil properties. Two types of forest were chosen which are riparian forest and inland forest. Two plots with the sizes of 5m x 10 m were built in each forest types and which means the total of area sampling in this study was 200m2. Result shows that a total of 885 individuals of herbal and non-tree plants were recorded from 68 species, 40 genera and 22 families. Riparian forest plot recorded 558 individuals from 55 species, 37 genera and 21 families while inland plot recorded 327 individuals from 36 species, 27 genera and 15 families. Significant difference was observed in soil physico-chemical properties, phosporus (P), electric conductivity (EC), nitrate (NO3 -), ammonium nitrate (NH4NO3 +), moisture content and organic matter (OM) between these two forest types. Based on Cannonical Correspondance Analysis (CCA) there was a strong relationship between species abundance and edaphic factors in the study site. Results from this study could contribute to new information on conserving and preserving the herbal and non-tree plants as the natural green asset of Terengganu and Malaysia.